“Y todavía me siento un anormal”. La definición discursiva del enemigo de las derechas argentinas, cerca de revoluciones posibles o profetizadas. 1916-1982 - Olga Echeverría (Nuevo mundo - Mundos Nuevos, 2020)
Argentine right-wings of the 20th century included a wide range of ideologies (nationalism, integralist Catholicism, Liberal-Conservatism, Military Authoritarianism) that understood inequality as a consubstantial and “natural” fact of the human order or as result of individual skills. They also coincided in the opposition to majoritarian democracy, in the sacralization of private property, the call to defend Western traditions and values, in some cases, the Republic as a shelter of the Civilization, and over all, the denouncement of a common, dark, pervert, and face-less enemy that allowed to the right-wings to identify themselves as a threatened “we”. That definition of internal enemy, with its own historical variations, recovered rhetorical ideas and symbols available in the collective imaginaries from the beginning of the 20th century in order to legitimate antagonism and the self-perception.